Rehabilitation Outcomes of Persons with Complete Paraplegia at a Private Rehabilitation Hospital - R. Henn; S. Visagie; G. Mji (AOSIS, 2012)
In order to overcome activity limitations, prevent secondarycomplications and early death and achieve community integration comprehensiverehabilitation post spinal cord injury (SCI), is essential. The aim ofthe study was to evaluate outcomes of patients with complete paraplegia whoreceived rehabilitation at a private rehabilitation hospital.A quantitative, descriptive methodology was implemented. All patientswith complete, traumatic, thoracic spinal cord injuries, admitted to the studyhospital in the study period, were consecutively sampled. Thirty five patientswere identified of whom16 adhered to the inclusion criteria. The FunctionalIndependence Measure (FIM ) and Needs Assessment Checklist (NAC) wereused as measuring instruments.The mean length of stay was 95 days. Discharge FIM motor scores ranged from 72 to 83 with a mean of 79.3. Themean gain in FIM motor score was 55 and varied from 45 to 61. Discharge NAC scores ranged from 264 to 340 with amean of 300 out of a possible 347. A correlation between length of stay and discharge FIM scores (p = 0.05) were found.Both NAC and FIM scores indicated high levels of physical independence. According to NAC scores patients wereeducated on the prevention of secondary complications and received psychological counselling. Discharge planningand community integration scored lower with means of 80% and 61% respectively. Community based completionof rehabilitation programmes, the incorporation of the NAC, or another participation outcome measure and implementationof on-going programme monitoring and assessment strategies is recommended.